Pan-Cancer Analysis of Head-to-Head Gene Pairs in Terms of Transcriptional Activity, Co-expression and Regulation - Chen, Yunqin; Li, Hong; Li, Yuan-Yuan; Li, Yixue (Frontiers in Genetics, 2021)
Background: Head-to-Head (H2H) gene pairs are regulated by bidirectional promoters and divergently transcribed from opposite DNA strands with transcription start sites (TSSs) separated within 1 kb. H2H organization is ancient and conserved, and H2H pairs tend to exhibit similar expression patterns. . Although some H2H genes were reported to be associated with carcinogenesis, little is known about the functional relevance and regulation mechanisms of H2H organization in the scenario of cancer development. Methods: Human H2H gene pairs were identified using GENCODE hg19 according to the definition and the functional relevance of H2H pairs was explored through function enrichment and semantic similarity analysis. To investigate the association of H2H organization and carcinogenesis, pan-cancer differential analysis of H2H genes about transcriptional activity, co-expression and transcriptional regulation by transcription factors and enhancers were performed using data from The Cancer Genome Atlas. Cox proportional hazards regression model and log-rank test were used to determine the prognostic powers of H2H pairs. Results: In the present study, we first updated H2H genes from 1447 to 3150 pairs, from which the peak group with TSS distance of 1-100 was observed as expected in our previous work. It is interesting that housekeeping genes, mitochondrial-functional associated genes and cancer genes tend to be organized in the H2H arrangement. Pan-cancer analysis indicates that H2H genes are transcriptionally active in both normal and cancer states, but H2H pairs are much more coherent transcriptionally correlated in cancer than in normal. Particularly, housekeeping H2H pairs differentially co-expressed between in cancer and normal much more significantly than non-housekeeping H2H pairs. Some differentially correlated H2H pairs have the potential to be prognostic biomarkers in multiple cancer types. The alteration of TF similarity contributes to differential co-expression of H2H pairs during carcinogenesis; meanwhile remote enhancers also partly explain the differential co-expression and co-regulation of H2H pairs. Conclusions:H2H pairs tend to show much stronger positive expression correlation in cancer than in normal due to differential regulation of bidirectional promoters. The study provides insights into the significance of H2H organization in carcinogenesis and the underlying dysfunctional regulation mechanisms.